Large‐scale climatic patterns and area affected by mountain pine beetle in British Columbia, Canada - Macias Fauria, M; Johnson, E (Wiley, 2009)
We present evidence of high spatial synchrony in an area affected by mountain pine beetle (MPB, Dendroctonus ponderosae) across large distances in British Columbia, Canada, in a study of a spatially explicit database of an area affected by MPB‐caused tree mortality for the period 1959–2002. We further show that large‐scale climatic patterns (Pacific Decadal Oscillation (PDO) and, to a lesser degree, Arctic Oscillation (AO)) are strongly related to the observed MPB synchrony, and that they probably operate through controlling the frequency of extreme cold winter temperatures that affect MPB larvae survival. A smaller portion of the data's variability is linked to the onset of the two largest outbreaks in the studied period and might be attributed to dispersal from outbreak‐prone areas or else to differences in microhabitat (e.g., host availability) in these regions. The onset of a warm PDO phase in 1976 favored MPB outbreaks by reducing the occurrence of extremely low winter temperatures province‐wide. Likewise, the exceptionally high and persistent AO values of the late 1980s and 1990s enhanced MPB activity in the southern and northern parts of the region. Summer warmth cannot be discarded as an important agent at smaller scales.